Delusional parasitosis: A case treated with low dose of risperidone - Çayköylü, Ali; Ekinci, Okan; Albayrak, Yakup; Kulo?lu, Murat (My University, 2011)
Delusional parasitosis (DP) is a rare psychiatric disorder which is characterized by the fixed and wrong belief as the person's body is infested with parasites although there is not an additional thought disorder or medical evidence. In this report, a 79-year-old woman who had thoughts about insects that were strolling on her skin and hair and that were invading all sides of her house and who did not improve with quetiapine and subsequently remitted with low dose risperidone was presented. Evidence regarding the use and the efficacy of atypical antipsychotics in DP is limited to case reports. It is reported that risperidone is the most effective agent in DP treatment among the atypical antipsychotics. In addition, several case reports have indicated the beneficial effects of risperidone in primary DP. In conclusion, when the treatment approach is selected in primary DP cases, as the side effects, patient compliance, and effectiveness must be evaluated at the same time and take into consideration the persistent nature of the illness.
Hezeyanî parazitoz: Düşük doz risperidon ile tedavi edilen bir vak'a
Keywords: Atypical antipsychotics; Delusional parasitosis; Quetiapine; Risperidone